LESSONS FROM PRIMARY HEALTH CARE IN THE UNITED KINGDOM - Dian Kusuma (Jurnal Administrasi Kesehatan Indonesia, 2021)
The health system in Indonesia is facing the persistent burden of maternal mortality and infectious diseases (including COVID-19) and an increasing burden of non-communicable diseases. Thus, health system reform and innovations at all levels are needed, including through lessons learned from other countries. There are at least five lessons from primary health care in the United Kingdom: easy access, digital and online services, continuity of care, managing chronic conditions, and referral and counter-referral system. There are lessons that policymakers and stakeholders at the national and local (city/district) level could potentially learn from. Despite the differences between the UK and Indonesia (e.g. country income level, national health systems), these lessons could be adapted or piloted in some settings.